AGRICULTURAL SYSTEMS – ROLE AND IMPORTANCE IN THE ENVIRONMENT PROTECTION AND SUSTAINABLE RURAL DEVELOPMENT IN BANAT, ROMANIA - Florin, Sala; Dobrei, Alin (Economics of Agriculture, 2018)
Researches were conducted in the Western area of the country, in the Banat Plain and concerned the sustainability of agricultural systems as production systems and means of sustainable rural development. Categories of use of the agricultural land in the county of Timis have suffered changes in the studied period with different amplitude from one category of use to another, also finding uncultivated and temporarily abandoned land. There were recorded changes in the structure of crop plants with implications on crop rotation and agricultural environment. In the studied viticulture systems we observed a high diversity of biological material but technologies show some malfunctions. During this period, the technical park has undergone an improvement both in number and quality even if an optimal level of endowment hasnt been reached yet. Through some indicators the increasing of performance and productivity of the agricultural systems are observed, but much too slow to ensure prosperity to farmers.